Force-sensitive resistors to measure the distribution of weight in the pads of sound dogs in static standing position - Choi, Chun-ki; Kang, Jinsu; Kim, Namsoo; Jeong, Soon-wuk; Heo, Suyoung (Austral Journal of Veterinary Sciences, 2022)
The purpose of this study was to measure how weight is distributed in the pads of each of the 4 limbs of dogs and evaluate the intra-investigator reproducibility and inter-investigator reliability of the measurement method. Eight dogs were examined 3 times a day by 3 investigators at 1 week intervals for 3 weeks to determine the weight distribution to each of the pads. The force-sensitive resistor was used for measurement and specific software (PetLAB2) was used to calculate the weight applied to each pad. The intra-investigator reproducibility showed moderate to good reliability (ICC range, 0.575-0.873) and the inter-investigator reliability was moderate (ICC range, 0.525-0.746). Based on this study, it can be observed whether the weight distributed to each pad approaches the normal value after treatment in patients with orthopaedic and neurologic diseases. It is expected that this experimental method will be one of the objective indicators to evaluate the degree of recovery in patients with orthopaedic and neurologic diseases.